A Fully Discrete Explicit Multistep Scheme for Solving Coupled Forward Backward Stochastic Differential Equations (Advances in Applied Mathematics and Mechanics, 2020)
In this work, we are concerned with the explicit multistep scheme for solving the coupled forward backward stochastic differential equations (FBSDEs). Based on the Lagrange interpolation and first-order derivative approximations, we will propose a fully discrete explicit high-order multistep scheme for solving coupled FBSDEs. Its high accuracy, efficiency and stability are verified by the numerical experiments.